PENGEMBANGAN MEDIA PEMBELAJARAN LKPD ELEKTRONIK (E-LKPD) INTERAKIF BERBASIS LIVEWORKSHEET PADA MATERI SUDUT KELAS V SDN 143 LEMO - Nur Adinda Ismi Azis; Suarti Djafar; Nadar (STKIP Subang, 2026)
The low level of students’ understanding of angle material, the lack of interactive learning media, and the use of conventional teaching methods became problems in mathematics learning for fifth-grade students at SDN 143 Lemo. These conditions caused students to be less active, easily bored, and have difficulty understanding abstract angle concepts. Therefore, interactive learning media were needed to improve learning quality. This study aimed to develop an interactive Electronic Student Worksheet (E-LKPD) based on Liveworksheet on angle material and determine its validity, practicality, and effectiveness. This research used the Research and Development (R&D) method with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The subjects were three validators and 20 fifth-grade students of SDN 143 Lemo. Data were collected through questionnaires, observations, documentation, and tests. The results showed that the interactive E-LKPD based on Liveworksheet was categorized as very valid, with average scores of 3.92 from media experts, 4.25 from material experts, and 5.00 from practitioners. The practicality test obtained average scores of 4.30 in the small group trial and 4.65 in the large group trial. The effectiveness test showed an N-Gain score of 0.53 in the moderate category. Therefore, the interactive E-LKPD based on Liveworksheet is feasible and effective for mathematics learning in elementary school.